Minor papilla approach improves technical success of nasopancreatic drainage-based pancreatic juice cytology for early pancreatic cancer diagnosis - Satoh, Tatsunori; Kawaguchi, Shinya; Takahashi, Haruna; Masui, Yuichi; Matsuda, Masanori; Kawai, Asami; Endo, Shinya; Kurokami, Takafumi; Shirane, Naofumi; Ohno, Kazuya (Endoscopy International Open, 2025)
Early detection of pancreatic cancer (PC) is vital for improving survival, yet it often relies on indirect imaging findings rather than detection of distinct masses. Recently, pancreatic juice cytology obtained via nasopancreatic drainage (NPD-PJC) has emerged as a valuable diagnostic approach for early-stage disease. However, technical challenges associated with NPD placement remain a significant limitation. This study aimed to assess whether incorporating a minor papilla approach improves the technical success rate for NPD-PJC in patients with suspected early-stage PC.We conducted a retrospective study of patients scheduled for NPD placement for NPD-PJC between January 2015 and November 2024. Demographic and procedural data were collected, including endoscopic retrograde pancreatography (ERP) findings and outcomes associated with major and minor papilla approaches. Potential risk factors for technical failure and post-ERP pancreatitis (PEP) were evaluated.A total of 81 cases were planned for NPD-PJC within the study period to differentiate early-stage PC. The success rate of the major papilla approach alone was 81.5%, which significantly increased to 93.8% (P = 0.00157) with the addition of the minor papilla approach. Abnormal ductal configurations were associated with failure of the conventional approach (odds ratio 23.4). The minor papilla approach was not a significant risk factor for PEP, whereas younger age (≤ 70 years) and high body mass index (≥ 25) were identified as PEP risk factors.Incorporating the minor papilla approach substantially improves technical success of NPD-PJC without increasing PEP risk, underscoring the importance of individualized ERP strategies for early-stage PC diagnosis.
Keywords: Pancreatobiliary (ERCP/PTCD); Diagnostic ERC; ERC topics; Quality and logistical aspects; Performance and complications